Electrostatically optimized adapalene-loaded emulsion for the treatment of acne vulgaris - Ji, Yun Bae; Lee, Hye Yun; Lee, Soyeon; Kim, Young Hun; Na, Kun; Kim, Jae Ho; Choi, Sangdun; Kim, Moon Suk (Materials Today Bio, 2022)
Adapalene (AD) is an FDA-approved drug that shows good therapeutic efficacy for the treatment of acne vulgaris. However, due to its negative charge, AD cannot efficiently penetrate across the also negatively-charged skin membrane. This study is the first to assess the treatment of acne vulgaris using electrostatically optimized AD emulsions prepared using anionic AD with methoxy polyethylene glycol-b-poly(ε-caprolactone) (MC) as an anionic emulsifier coupled with a newly synthesized MC with different contents of an amine pendant-group (MC-[NH2]x) as a cationic emulsifier. The AD emulsion prepared using MC-[NH2]x with high cationic charge potential was significantly stable in the short-term studies compared with anionic MC or no emulsifier. Furthermore, the AD emulsion prepared with the cationic MC-[NH2]x emulsifier provided a two or three times stronger therapeutic effect against acne vulgaris than the AD emulsion prepared with the anionic MC emulsifier or no emulsifier in an animal study. Additionally, the AD emulsion with high cationic charge potential exerted a remarkable inhibition of macrophage expression, as confirmed by histological analysis. Therefore, the electrostatic interaction between the negatively-charged skin membrane and the AD emulsion prepared with the cationic MC-[NH2]x emulsifier provides a promising therapeutic strategy for acne vulgaris.
Keywords: Acne vulgaris; Adapalene; Cationic charges; Cationics; Charge potentials; Electrostatic emulsifier; Methoxypolyethylene glycol; Negative charge; Negatively charged; Therapeutic efficacy; Acne vulgaris; Adapalene; Electrostatic emulsifier; Electrostatic interaction; Emulsion